Adverse childhood experiences, stress, and emotional availability: an American Indian context - Saunders, Hannah E., author; Biringen, Zeynep, advisor; MacPhee, David, committee member; Swaim, Randall, committee member; Sarche, Michelle, committee member (Colorado State University. Libraries, 2016)
American Indian individuals are at a heightened risk for experiencing trauma and high levels of life stress. Despite a preponderance of research demonstrating the long-term detrimental effects of early trauma on physical and mental health, no study has yet examined how caregivers' own traumatic experiences impact their children's social-emotional health. The primary purpose of this study was to examine the degree to which caregivers' trauma, stress, and mental health was associated with child social-emotional functioning. Results indicated that caregivers' early traumatic experiences have long-term effects on their own mental health, as well as their child's. These findings highlight the importance of assessing and intervening upon the effects of early life trauma. The secondary purpose of this study was to validate the Emotional Availability Scales, a measure of the parent-child relationship quality, in an American Indian/Alaska Native community. Results demonstrated that higher emotional availability, particularly structuring, was related to children's social-emotional competence, and lower caregiver non-hostility was associated with child externalizing symptoms. These results call attention to the relevance of multiple indicators of the quality of caregiver-child relationships, rather than a sole focus on sensitivity.